Once Upon A Princess: The Construction of Princesshood in The Disney Princess Animated Film - Gissena, Annisa; Agusta, Rivga (CV. Publikasi Indonesia, 2025)
Disney Princess films, such as Cinderella (1950), Snow White and the Seven Dwarfs (1937), and Beauty and the Beast (1991), are global cultural phenomena that influence children's perceptions of royalty. In Indonesia, this depiction has become more prominent among children than traditional royal figures, such as local princesses from historical contexts, raising concerns about shifting local cultural narratives. This study explores how Disney Princess films construct the concept of a princess as a royal symbol, focusing on depictions of royalty through visual and narrative elements. Using Roland Barthes' semiotic framework, this qualitative research conducts an in-depth analysis of the denotative, connotative, and mythical meanings in certain scenes in all three films. Data were collected by observing and documenting visual representations, transcribing relevant dialogues, and applying Barthes' concepts of textual meaning to connect findings to broader cultural narratives. The analysis of this study reveals that the Disney Princess films construct the princess character as a symbol of nobility through characteristics such as physical beauty, kindness, empathy, and social status. These characteristics are naturalized into society's expectations of the definition of a princess, thereby perpetuating Western ideals of royalty. These findings highlight the dominance of global media narratives that can mask local cultural representations. This research contributes to the study of media and culture by revealing the hegemonic influence of Disney Princess films on children's perceptions of the royal family. It emphasizes the need for more inclusive media representation that respects local traditions and encourages a richer understanding of cultural diversity among younger generations.